TORAKOCHIRURGIAPulmonary resection in patients after pneumonectomy for bronchogenic carcinoma - Tomaszewski, Dariusz; Sternau, Adam; Łapiński, Mariusz; Rzyman, Witold (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Background: Patients after pneumonectomy for bronchogenic carcinoma are at risk of cancer in the contralateral lung. The occurrence of a second cancer on the remaining lung after pneumonectomy poses unique treatment problems. Surgery is often considered contraindicated. Aim: We report the outcome of patients who were operated on for lung cancer after pneumonectomy performed for lung cancer. Material and Methods: Between 1987 and 2007 six NSCLC patients (4 men and 2 women) who had previously undergone pneumonectomy were operated on for second cancer in the remaining lung. Results: All patients were asymptomatic. Second cancers were discovered on surveillance chest roentgenograms. Performance status was 0 on the Zubrod scale in all patients. Median preoperative FEV1 was 1.53 L (range 1.27-1.83). Seven resections in 6 patients (one patient with two resections) were performed between the 5th and 192nd month after pneumonectomy. One wedge resection in 4 patients, two wedge resections in one patient and trisegmentectomy in one patient were performed. One patient died after trisegmentectomy (16.6%) due to respiratory insufficiency. No other complications were observed. One patient is alive 46 months after additional resection with evidence of cancer. One patient, after two wedge resections, died 95 months after the first wedge resection due to cardiac failure. Three patients died respectively after 14, 16, 21 months, all with recurrent lung cancer. Median survival was 18.5 months. Conclusions: Patients who have lung cancer in the residual lung after pneumonectomy should not be automatically excluded from surgery. A highly selected group of these patients may achieve an acceptable survival rate with a low operative mortality and morbidity.